2017
DOI: 10.1128/jvi.00194-17
|View full text |Cite
|
Sign up to set email alerts
|

Serine 235 Is the Primary NS5A Hyperphosphorylation Site Responsible for Hepatitis C Virus Replication

Abstract: The nonstructural protein 5A (NS5A) of the hepatitis C virus (HCV) is a phosphoprotein with two phosphorylation states: hypo-and hyperphosphorylation. Genetic mutation studies have demonstrated a cluster of serine residues responsible for NS5A hyperphosphorylation and functions in viral replication and assembly; however, the phosphorylation levels and potential interactions among the serine residues are unclear. We used three specific antibodies to measure NS5A phosphorylation at S222, S235, and S238 that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(55 citation statements)
references
References 40 publications
(78 reference statements)
6
47
1
Order By: Relevance
“…Our data are consistent with this (Fig 5) and we propose a model whereby S225 phosphorylation primes subsequent phosphorylation in a bidirectional fashion. Confirmation of this model would require use of additional phospho-specific antibodies, such as those used by Yu et al (33) to demonstrate that S238 phosphorylation is dependent on S235 phosphorylation. This observation is consistent with our findings and the model proposed in Fig 13.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our data are consistent with this (Fig 5) and we propose a model whereby S225 phosphorylation primes subsequent phosphorylation in a bidirectional fashion. Confirmation of this model would require use of additional phospho-specific antibodies, such as those used by Yu et al (33) to demonstrate that S238 phosphorylation is dependent on S235 phosphorylation. This observation is consistent with our findings and the model proposed in Fig 13.…”
Section: Discussionmentioning
confidence: 94%
“…We proceeded to use the antiserum to investigate which cellular kinases might be responsible for phosphorylation of S225. Previous studies (29, 33, 38), coupled with bioinformatic analysis (39), suggested that S225 was a potential phosphorylation site for three kinases: casein kinase-Iα (CKIα), polo-like kinase-1 (PLK1) and glycogen synthase kinase-3β (GSK3β). To investigate their potential roles in phosphorylation of S225, we treated HCV-infected Huh7 cells with three selective kinase inhibitors: D4476 (CKIα inhibitor); SBE13-HCl (PLK1 inhibitor), or GSK-3β Inhibitor VIII (GSK3β inhibitor).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzed with SDS-PAGE plus immunoblotting, NS5A appears as two bands at 56 and 58 kDa, which represent, respectively, hypo-and hyperphosphorylated forms of NS5A (10). Numerous studies have pinpointed a cluster of eight highly conserved serine residues (S222, S225, S228, S229, S230, S232, S235, and S238) in the LCS I region responsible for NS5A hyperphosphorylation (11)(12)(13)(14)(15)(16)(17)(18). Mutations in some of these serine residues reduce NS5A hyperphosphorylation in association with effects on viral replication and assembly (11,12).…”
mentioning
confidence: 99%